Asean's defence diplomacy: the road to Southeast Asian defence community? - Pedrason, Rodon (2015)
The purpose of this study is to examine whether the practice of ASEAN member states’ defence diplomacy through practical defence cooperatives for handling security challenges in Southeast Asia contains the characteristics of a defence community which could pave the way for the formation of a future Southeast Asian defence community. The security challenges facing the countries of Southeast Asia today lie in creating a stable environment. The debate over the concept of security has broadened the discourse on regional security cooperation, which drives states to engage more deeply in multilateral diplomacy in order to defend better and promote their national interests, and particularly in handling problems in maintaining a stable peace in the region. As the unit of analysis, this study examined the forum of the ASEAN Defence Ministers’ Meeting (ADMM) and ASEAN Defence Ministers’ Meeting Plus (ADMM-Plus), and selects six ASEAN member states as the loci of the study, namely: Brunei, Indonesia, Malaysia, Singapore; Thailand and Vietnam. The different forms of government system became the reasons for selecting these six countries, i.e. a democratic state such as Indonesia, a semi-authoritarian system such as in Malaysia and Singapore, a monarchy as in Brunei and Thailand, socialist countries such as Vietnam. However, only four out of the six chosen countries were founding members of ASEAN. This study proposes two central questions. The first question focuses on the development of forms of threats found in Southeast Asia today, which encourages ASEAN member states to conduct defence diplomacy, while the second question focuses on whether the implementation of ASEAN defence diplomacy helps to shape an ASEAN defence community. In answering those questions, this study is applying qualitative methodology to address an explanatory aspect of these questions, and using the theory of regionalism through presenting empirical evidence of ASEAN member states practical defence diplomacy. It seeks to show how ASEAN member states develop their military role in handling new emerging non-traditional security threats contain the characteristics of a defence community which could pave the way for this regional organisation to turn into a collective defence grouping.
Keywords: Hochschulschrift; Sicherheitspolitik; Südostasien; Association of Southeast Asian Nations